Childhood adversity and cell-mediated immunity in young adulthood: Does type and timing matter? - Slopen, Natalie (2012)
Childhood adversity can have powerful effects on health over the life course. Persistent changes in cell-mediated immune function may be one pathway linking adverse childhood experiences with later disease risk. However, limited research has examined childhood adversity in relation to cell-mediated immune function, and in particular, immune response to latent viruses in adulthood. The present study investigated the association of two types of childhood adversity, socioeconomic disadvantage during adolescence and abuse prior to age 18, with Epstein–Barr Virus (EBV) antibody titers in a large nationally representative sample of young adults aged 24–32 years. Data were drawn from the National Longitudinal Study on Adolescent Health, Wave 4 (n = 13,162). We examined the associations of three indicators of adolescent SES (parental education, household income, and occupational status) and frequency and timing of physical and sexual abuse with EBV antibodies, controlling for age, sex, race/ethnicity, and presence of a smoker in the household during adolescence. Lower parental occupational status and some categories of lower education were associated with elevated EBV antibodies (p < .05), and individuals who reported sexual abuse that occurred more than 10 times had elevated EBV antibodies relative to individuals who were not sexually abused (p = 0.03). Among individuals exposed to physical abuse, those who were first abused at age 3–5 years had heightened EBV antibodies relative to those first abused during adolescence (p = 0.004). This study extends prior research linking early adversity and immune function, and provides initial evidence that childhood adversity has a persistent influence on immune responses to latent infection in adulthood.